Thrust optimization of linear oscillatory actuator using permeance analysis method - Abdul Shukor, Fairul Azhar; Misron, Norhisam; Mailah, Nashiren; Zare, Mohamad Reza; Wakiwaka, Hiroyuki; Nirei, Masami (2011)
This paper is described on optimization the thrust of linear oscillatory actuator (LOA). The objective of this optimization is to obtain the high thrust of LOA with restricted weight of LOA to make sure it operates at highest as possible the thrust while maintain it mobility features. Thus, the LOA is aim to have a starter thrust higher than 200 N while having total of weight lower than 2.0 kg. The thrust optimization is done using permeance analysis method (PAM). The thickness of the permanent magnets and the height of coils have been optimized at various total of radius of LOA in order to obtain the optimized structure of LOA. The optimized structure of LOA was decided by using two different methods. The first method is by evaluating the calculation output. The second method is by using generic algorithm. Both output of these method giving a different result in term of LOA PM’s thickness however having similar value of characteristics. The FEM and measurement results were used to verify the PAM output. Consequently, the LOA has been designed with optimum parameters which having value of starter thrust of 245 N and the total of weight is 2.0 kg .